Anterior cruciate ligament graft healing by peptide-based vascular endothelial growth factor and bone morphogenetic protein recruitment - Wouter Van Genechten; Mario Hevesi; Nicholas Olson; Mason Carstens; Aaron J. Krych; Peter Verdonk; Andre J. van Wijnen; DBF Saris (Elsevier, 2021)
ABSTRACT: Introduction: The frequency of adverse outcomes after revision ACLR emphasizes the importance of the primary reconstruction regarding intra-articular graft healing and tunnel osteointegration. Objectives: The objective was to generate a functionalized suture based on peptide attachments that spatially recruits VEGFs and BMPs for graft healing. It was hypothesized that the suture would capture cytokines with favorable graft-bone integration in an ACLR rabbit model. Methods: Suture functionalization with established peptides was tested by immunofluorescence (IF) for recombinant VEGFA and BMP2. Three rabbit groups (n = 12/group) underwent ACLR using either a dual functionalized, plain suture (DF vs suture groups) or no suture (tendon group). Outcomes were assessed by μCT, molecular analysis, histology, and biomechanics at 4 to 12 weeks postoperatively. Results: Adequate functionalization was verified by IF for both growth factors. In vivo, the bone mineral density trended towards an increase at 4 weeks in the DF group (P > .194) but not at 12 weeks. Healing was better in the mid-section bone tunnel areas of the tendon group at 12 weeks compared to the suture (P = .026), or DF group (P = .011). Molecular analysis was inconclusive. Accumulation of growth factors was not evident by immunohistochemistry. Biomechanics showed no intergroup difference. Conclusions: The study established the development of a suture capable of capturing BMP2 and VEGFA by a peptide-binding strategy. This technology did not show superior tissue response or changes in biological parameters of ingrowth in vivo but seems to be interfering with bone tunnel closure at 12 weeks. The current model and technology should be further optimized.